Kinh nghiệm quốc tế hóa giáo dục đại học của một số nước trên thế giới: Bài học cho Việt Nam. - Trần Mai, Đông; Lê Nhật, Hạnh; Phùng Vũ Bảo, Ngọc; Mai Trường, An (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The last decade has experienced the emergence of mainstreams in higher education. One of those is internationalization. This calls for a deep understanding of this term, which needs to make sense of the varied and complex ways of the globalization process; especially, with a focus on higher education. This study is conducted to offer a comprehensive overview of many perspectives on internationalization and university governance to give better autonomy to higher education institutions. This research also highlights the sharing number of international experiences and lessons in several developed countries to suggest tentative implications in the context of Vietnamese higher education. The study findings will not only supply insights into internationalization in university governance for multiple stakeholders, but also bring the universities better changes for development and integration.
Keywords: Internationalization; Higher education; Vietnamese higher education